A shockwave analysis of foreign exchange markets during Brexit and Covid-19 - Li, Shiyun (2021)
The two recent international issues Brexit and COVID-19 pandemic caused serious shockwaves in the foreign exchange markets and other financial industries. This paper is tried to address how traditional and safe-haven currencies worked in the foreign exchange market experienced during Brexit and COVID-19. The correlation test, unit root test, VaR models, and Diebold-Yilmaz volatility spillover analysis were employed in the research. Based on the Diebold-Yilmaz volatility spillover analysis, the calculated results demonstrated that the shockwaves caused by COVID-19 are 1.2 times higher than that of Brexit, and the British pound changed from a spillover transmitter to a receiver. The Swiss franc showed less safe-haven effects during COVID-19 than Brexit. However, the Japanese yen showed a stronger ability to prevent risks and even earning profits under volatilities, which made it be a more ideal safe-haven currency.